The Paradigm of Science Education: an Attempt of Philosophical and Conceptual Foundations Explication - Aleksandrova, Yuliia (Studia Warmińskie, 2021)
The article presents the issues related to the science teaching paradigm, which extends the traditional understanding of the goal of education as an experience of humanity acquired through continuous progress and development. It has been proven that J. Dewey’s pragmatic philosophy, like all contemporary epistemology, assumes that the cognitive goal of the processes of establishing and confirming meaning is a valuable and pragmatic confrontation of the acquired knowledge. It follows that there are specific philosophical positions in the research process: subjectivism as an individual search for an innovative way to solve a problem, and objectivity, reflecting the de-personification of experimental procedures and methods, and consensus in this context means using a formalized language to publish the results. According to the principles of constructivism, the process of education itself should be treated as a construction of a certain type of worldview, evaluation, and behavior. Learning, in line with the science teaching paradigm, is the concretization and interpretation of society’s enduring discursive practices. The educational process is an interaction in determining a collective way of defining and understanding phenomena and processes. In science education, it is postulated to reject the traditionally established practices of academic theorizing and adopt the position of authority uncritically. Instead, there is a problematization of the fundamental discourse.